Balanced Scorecard as a tool for sport managers. An approach from Cuban baseball - Ramos Acevedo, IN.; Madrigal Castro, AD.; González Quesada, O.; Figueredo Toledano, RW.; Rodríguez-Gallo Martínez, Y.; Barroceta de Rojas, CR.; Gómez Tejeda, Y. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The study of Management as a Science and its contextualization in the sport field is essential at present for the success of the sport managers. Previously only certain kinds of game indicators were considered in the evaluation of the team results but today new horizons are opened to other perspectives. The use of the Balanced Scorecard as a tool to translate the strategy into actions and also for the control management in the organizations has been extended all over the sport world. It also enables the control and evaluation of some aspects as the motivation and the preparation of the athletes and technicians, the perception and the satisfaction of the fans, the fulfillment of the social responsibility or the financial results. This article is the result of some reflections, experiences and the literature review, allowing an approach to the current Cuban baseball context.